PENGARUH E-PROMOTION STRATEGIC TERHADAP PEMBELIAN - Ni Nyoman Suarniki; Rizki Amalia Afriana (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of e-promotion (context, communication, collaboration, connection) on purchases. A case study at the Banjarmasin Ero Optik Store. This study uses a quantitative approach. The population consists of all Instagram followers @erooptikbjm. The research sample was determined as many as 100 responden, where 50 respondents are selected by incidental sampling method. Data processess by using Multiple linear regression data analysis technique with the help of SPSS software version 22.0. The results of this study indicate, partially context variables (X1), communication (X2), collaboration (X3) have a significant influence on consumer purchases. However, the connection variable (X4) has no significant effect on consumer buying interest. Simultaneously the variables context (X1), communication (X2), collaboration (X3) and connection (X4) have a significant influence on consumer buying interest. The communication variable (X2) has the most dominant influence on consumer buying interest. This means that technological advances can be utilized by marketers and buyers to transact more easily, quickly, cheaply and practically through social media. Variable connection does not have a significant effect because in the transaction of goods, a connection is not required. The most important thing is communication as in the results of the statistical coefficient beta of the communication variable which is the most dominant or most influential on consumer decisions to buy products. Discussion, good communication through intensity and well targeted media, can be developed into good relations between buyers and marketers, thus, supported by appropriate product specifications, the connection/relationship may have a major contribution to purchasing.